ANALYSIS OF PARAMETERS OF THE EXTERNAL CHARGE CASING FOR EFFICIENT DIRECTIONAL ROCK SPLITTING - SСHIPANOV, IGOR; SOLOVEI, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article emphasizes the selection of parameters for the external casing of an extended spacing explosive material to ensure effective and safe execution of explosive operations in the mining and extraction industry. The study examines and analyzes how the effectiveness of directional rock fracturing depends on various factors, including the type of explosive material, the shape and size of the explosive charge, parameters of the external casing of the explosive, as well as the geological characteristics of the rock formations. The choice of material for the external casing is discussed as it directly impacts its strength and resistance to loads. To achieve efficient energy transmission during the explosion and reduce the risk of casing rupture, it is suggested to calculate the optimal thickness. Using the heat conduction equation, the minimum thickness that prevents overheating of the casing can be determined. Ensuring the casing's hermeticity is crucial for the stability of the explosive material and to prevent unintended detonation. The hermeticity level can be determined using the formula presented in the study. For precise rock fracturing, the use of a remote initiating mechanism is proposed, which triggers at a specified moment. To enhance uniform initiation of the explosive material, a structural solution of initiator placement within the explosive charge is suggested.The presence of cracks and defects in the rock formation is highlighted as an important consideration in the development of casings for effective fracturing. It is known that when a cylindrical explosive charge is detonated within a homogeneous rock mass, three different zones are formed: the area of intense fracturing (fragmentation), the zone of crack formation (radial cracks), and the area of elastic deformation. Based on conducted research, the article presents a formula that takes into account both the main properties of the rock mass (strength characteristics and fissuring) and the parameters of blasting operations, namely the charge radius and explosive material properties. Using the example of the iron ore quarry's geological conditions, calculations were performed for the radii of blast-induced fracturing zones when detonating borehole charges within fractured rock masses at different distances between natural cracks.
Keywords: directional fission; external stain; explosion; explosives; explosive detonation zone; intensive crushing; massif; cracking; explosive works; the radius of the cracking zone